Selected clinical highlights from the 2012 ERS congress in Vienna - Marvisi, Maurizio; Herth, Felix; Ley, Sebastian; Poletti, Venerino; Chavannes, Niels H.; Spruit, Martijn A.; Clini, Enrico; Cottin, Vincent (The European respiratory journal, 2013)
This article reviews a selection of scientific presentations at the 2012 European Respiratory Society Annual Congress in Vienna, Austria. The best abstracts from the groups of the Clinical Assembly (Clinical Problems, Rehabilitation and Chronic Care, Imaging, Interventional Pulmonology, Diffuse Parenchymal Lung Disease, and General Practice and Primary Care) are presented and discussed in the context of the most up-to-date literature. The reviewed topics especially deal with the areas of chronic obstructive pulmonary disease (acute exacerbations, comorbidities, prognosis and rehabilitation), the diagnosis and management of idiopathic pulmonary fibrosis, sarcoidosis, endobronchial techniques in emphysema, functional imaging and issues in respiratory medicine relevant for the primary care setting, including aspects related to end-of-life care and palliation.
First published online: Dec 06 2012
Gesehen am 24.06.2021